Feasibility of simultaneous surface topography and XRF mapping using Shear Force Microscopy. (7th February 2012) - Dehlinger, M.; Dorczynski, C.; Fauquet, C.; Jandard, F.; Tonneau, D.; Bjeoumikhov, A.; Bjeoumikhova, S.; Gubzhokov, R.; Erko, A.; Zizak, I.; Pailharey, D.; Ferrero, S.; et al.
Marketed sources equipped with polycapillary optics allow now laboratory X–Ray Fluorescence (XRF) analysis with 5–10 µm lateral resolution. To improve it, we had the idea to use a thin cylindrical X–ray capillary fitted to the XRF detector. The combination with near–field microscopy would then lead to a simultaneous record of both topography and XRF from a sample at µm lateral resolution. For this purpose, we have built a home–made Shear Force Microscope to carry out this experiment in the future.In a first step, we have validated the microscope, operating in SNOM configuration, using test sample consisting in ZnO clusters deposited on a Si3 N4 grating. Second, the feasibility of XRF collection through a thin X–ray cylindrical capillary on Co/Ti sample is shown in this work. The results suggest that sub–1 µm in–lab XRF analysis is possible, replacing the optical fibre of our SNOM apparatus by an X–ray capillary. On the basis of modelling our results, we then further discuss the possibility to reach 100 nm XRF resolution, combined to surface topography, working in synchrotron environment.